On conditions for oscillation and nonoscillation of the solutions of a semilinear second-order differential equation - Evtukhov, V. M. (Ukrains’kyi Matematychnyi Zhurnal, 1994)
We establish sufficient conditions for oscillation and nonoscillation of regular solutions of the secondorder differential equation $y'' + p(t)|y|^{1-\lambda} |y'|^{\lambda} \,{\text {\rm sign }}\, y = 0$, where $λ < 1$ and $p: [a,ω[→ ℝ,\, −∞ < a < ω ≤ +∞$ is a locally summable function.